Ramachandran Chart: Validating Proteins Through a Three- Dimensional Structure. - Linhares, Micaely; Kelry Costa Guimarães, Dyuly; Santos, Kethelin Vitória Zaire dos; Barros, Henrique Lopes de; Miranda, Marcio Rodrigues; Silva, Kaio Alexandre da (International Journal for Innovation Education and Research, 2022)
A few years ago, validating proteins to see if they were good or bad was a process that took years. With the creation of the Ramachandran Graph that evaluates protein structures through the angles φ (phi) and ψ (psi), this task became less onerous. With the evolution of computing and bioinformatics, platforms have been created to generate Ramachandran graphs in an online manner, however, the platforms have a high degree of usability complexity. The system proposed by this project puts the user as the center of the development, developing a system that can generate the Ramachandran graphs from the files sent, make the outlier analysis and return to the user through e-mail communication when the activities are finished.